Relationship between political behaviour, intention to quit, and negligent behavior :|bthe mediating role of job satisfaction - Dancy, anak Jimmy. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This study was conducted to examine the mediating effect of job satisfaction in the relationship between political behavior and intention to quit and negligent behavior. A survey method was used to gather 121 usable questionnaires from a sample of employees in Radio Television Malaysia (RTM), Sarawak. Outcomes of hypothesis testing using Stepwise Regression analysis showed that the inclusion of job satisfaction into analysis had increased the effect of political behavior on intention to quit, but job satisfaction had not increased the effect of political behavior on negligent behavior. This result demonstrates that job satisfaction does act as a partial mediator in the political behavior models among employees in RTM. This fmding is in line with finding from past researchers conducted in Western countries. In addition, the implications of this study to the theory and practice, methodological, and conceptual limitations, as well as directions for future research are elaborated in this paper.